2014
DOI: 10.1177/016146811411600602
|View full text |Cite
|
Sign up to set email alerts
|

Asian American Education and Income Attainment in the Era of Post-Racial America

Abstract: Background Prevailing perceptions of Asian Americans as model minorities have long situated this population within postracial discourse, an assumption that highlights their educational success as evidence of the declining significance of race and racism, placing them as models of success for other people of color. Despite evidence to repudiate the model minority thesis, the visibility of Asian Americans in higher education continues to reinforce essentialist paradigms about their presumed success while renderi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…For model minority myths and stereotypes , studies covered three areas: (a) race/ethnicity differences on perceptions of the police (Y. Wu, 2014), perceptions of leadership (Festekjian et al, 2014), and employment discrimination (Covarrubias & Liou, 2014; Kushins, 2014); (b) Muslim Americans’ experiences post-9/11, such as perceptions of stigma (Khan, 2014) and experiences of ethnic prejudice (North et al, 2014); and (c) Asian Americans’ attitudes or reaction to racial discrimination (Son, 2014), perpetual foreigner stereotype (Tsuda, 2014), and exceptionalizing stereotype (i.e., being treated as an outlier of Asian Americans, A. G. T. T. Tran & Lee, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For model minority myths and stereotypes , studies covered three areas: (a) race/ethnicity differences on perceptions of the police (Y. Wu, 2014), perceptions of leadership (Festekjian et al, 2014), and employment discrimination (Covarrubias & Liou, 2014; Kushins, 2014); (b) Muslim Americans’ experiences post-9/11, such as perceptions of stigma (Khan, 2014) and experiences of ethnic prejudice (North et al, 2014); and (c) Asian Americans’ attitudes or reaction to racial discrimination (Son, 2014), perpetual foreigner stereotype (Tsuda, 2014), and exceptionalizing stereotype (i.e., being treated as an outlier of Asian Americans, A. G. T. T. Tran & Lee, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…For model minority myths and stereotypes, studies covered three areas: (a) race/ethnicity differences on perceptions of the police (Y. Wu, 2014), perceptions of leadership (Festekjian et al, 2014), and employment discrimination (Covarrubias & Liou, 2014;Kushins, 2014); (b) Muslim Americans' experiences post-9/11, such as perceptions of stigma (Khan, 2014) and experiences of ethnic prejudice (North et al, 2014); and (c) Asian Americans' attitudes or reaction to racial discrimination (Son, 2014), perpetual foreigner stereotype (Tsuda, 2014), and exceptionalizing stereotype (i.e., being treated as an outlier of Asian Americans, A. G. T. T. . A. G. T. T. Tran and Lee (2014) found that participants evaluated their partner, the interaction, and future interaction less favorably when they were told by their partner, "You speak English well for an Asian" (high racially loaded condition, exceptionalizing stereotype) than when they were told, "You speak English well" (low racially loaded condition) or, "Nice talking to you" (control condition).…”
Section: Viruses: Hepatitis B Virus (Hbv) Immunodeficiency Virus (Hiv...mentioning
confidence: 99%
“…In this regard, recent literature has criticized the monolithic image of the model minority stereotype in terms of students’ educational outcomes (e.g., Covarrubias & Liou, 2014; Lee, 2006; Nguyen et al, 2019; Ocampo & Soodjinda, 2016). In the United States, for example, most Southeast Asian populations age 25 and older, including Cambodian (16.4%), Laotian (18.0%), Hmong (18.4%), Burmese (21.3%), and Vietnamese (29.5%), attained bachelor’s or higher degrees at rates significantly lower than the average of the national population (31.3%) in 2016, whereas several other Asian American groups such as Asian Indian (74.2%), Korean (56.3%), Pakistani (56.2%), Chinese (55.4%), and Japanese (51.6%) reported overall higher figures (Snyder et al, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Many studies of Asian American income inequality focus on the generation differences in income among immigrants. Following Alejandro Covarrubias and Daniel D. Liou (2014), we include information on respondent citizenship and nativity and use both to create proxies for these generational differences. For the citizenship variable, the CPS collects information about whether respondents are "U.S. Citizen," "Born in U.S., outlying," "Born abroad of American Parents," "Naturalized Citizen," and "Not a U.S.…”
Section: Control Variablesmentioning
confidence: 99%